Spontaneous congenital non-pigmented epithelial cysts of the iris stroma. - Paridaens, A D (1992)
Histopathological and immunohistochemical findings in 11 patients with spontaneous congenital non-pigmented epithelial cysts of the iris stroma were studied. The cysts were lined by stratified squamous to unilayered cuboidal non-pigmented epithelium. Goblet cells were present in nine cysts, indicating a similarity to conjunctival epithelium. The demonstration of higher-molecular-weight keratins and absence of S-100 protein, by monoclonal and polyclonal antibodies, argues for surface ectodermal rather than neuroectodermal origin of the cysts. Theories of embryogenesis have been conflicting, but our results support the theory that they arise from surface ectoderm, displaced probably at the time of lens vesicle formation. The finding of normally sited subepithelial S-100 positive melanocytes may suggest that ectopic conjunctival epithelium can induce normal patterns of migration of neural crest cells.